2013
DOI: 10.31129/lumat.v1i3.1105
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Working Methods and Lower Secondary School Students’ Performance and Attitudes towards Biology

Abstract: Tiivistelmä Tutkimuksessa selvitettiin perusopetuksessa käytettyjen opetusmenetelmien ja oppimisympäristöjen yhteyttä oppilaiden biologian oppimistuloksiin ja asenteisiin biologiaa kohtaan oppiaineena. Tutkimuksessa on käytetty Opetushallituksen vuonna 2011 toteutetun luonnontieteiden kansallisen arvioinnin survey -aineistoa. Lomaketutkimukseen osallistui 2989 yhdeksäsluokkalaista oppilasta 133 koulusta. Biologian osaaminen oli selkeästi yhteydessä positiiviseen asennoitumiseen biologiaa kohtaan eli biologiast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Juuti et al (2010) report that classes often involve front of class teaching, reading from textbooks, and solving basic problems. However, Uitto and Kärnä (2014) found that students favor front of class teaching, and that methods where the teacher leads the lesson, explains, and discusses complex problems with students lead to a higher preference for natural science subjects (though not necessarily to better results). Yli-Panula and Matikainen (2014) identified school as the primary source of information about nature for Finnish students, followed by media and then family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juuti et al (2010) report that classes often involve front of class teaching, reading from textbooks, and solving basic problems. However, Uitto and Kärnä (2014) found that students favor front of class teaching, and that methods where the teacher leads the lesson, explains, and discusses complex problems with students lead to a higher preference for natural science subjects (though not necessarily to better results). Yli-Panula and Matikainen (2014) identified school as the primary source of information about nature for Finnish students, followed by media and then family.…”
Section: Discussionmentioning
confidence: 99%
“…This resonates with the research intent of this study and the literature cited in the introduction. The importance of connecting curriculum content with students' everyday lives has been long emphasized by many studies, including those aforementioned authors, as well as other Czech studies (e.g., Blažek & Příhodová, 2016;Rajsiglová & Poneszová, 2020) and also Finnish studies (e.g., Kang & Keinonen, 2018;Kang et al, 2019;Loukomies et al, 2013;Niemi et al, 2015;Uitto & Kärnä, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation